Comparison of Robotic versus Conventional Selective Neck Dissection and Total Thyroidectomy for Papillary Thyroid Carcinoma. (June 2016) - Song, Chang Myeon; Ji, Yong Bae; Sung, Eui Suk; Kim, Dong Sun; Koo, Hye Ryoung; Tae, Kyung
Objective: To compare the surgical outcomes of robotic selective neck dissection (SND) with total thyroidectomy and conventional transcervical SND with total thyroidectomy. Study Design: Case series with chart review. Setting: University tertiary care facility. Subject and Methods: We retrospectively analyzed 66 patients who underwent total thyroidectomy with SND (≥3 levels of II-V) and bilateral central neck dissection for cN1b papillary thyroid carcinoma, of whom 41 underwent conventional SND and 25 of whom underwent robotic SND. Subjective pain, sensory change, and cosmetic satisfaction were evaluated regularly for 3 months with a questionnaire. Results: Compared with the conventional group, patients in the robotic group were younger (mean, 36.7 vs 47.5 years; P = .003) and more female dominant (96.0% vs 73.2%; P = .023). Mean total operative time was longer in the robotic group than the conventional group (298 vs 236 minutes; P < .001). Anterior chest pain was higher in the robotic group at postoperative 1 day (pain score, 1.88 vs 0.62; P = .011), 1 week (1.30 vs 0.43; P = .036), and 1 month (0.90 vs 0.18; P = .029). Postoperative cosmetic satisfaction was significantly superior in the robotic group. Conclusion: Compared with conventional transcervical SND with total thyroidectomy, robotic SND with total thyroidectomy yields superior outcomes for cosmetic satisfaction, longer operative time, and higher chest pain in the short term. Further study with a larger number of patients is mandatory.